MEMBANGUN KARAKTER GENERASI Z MELALUI TRILOGI SANTRI DALAM KONTEKS PENDIDIKAN ISLAM MODERN - Fathor Rozi; Ayu Meliana; M. Aqil Fahmi Sanjani; Musammil Lateh (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2026)
This study aims to examine the character formation of Generation Z through the implementation of the Santri Trilogy in the context of modern Islamic education in the Zaid bin Tsabit (K) area of ​​Nurul Jadid Islamic Boarding School. The approach used is qualitative with data collection techniques through observation, interviews with Islamic boarding school administrators, foster parents, alumni, and students, and documentation of learning activities. The results of the study indicate that the process of internalizing the values ​​of the Santri Trilogy, which include the obligation of fardhu 'ain, the attitude of self-awareness from major sins, and noble behavior towards Allah and creatures, is able to increase the active involvement of students in learning, develop information literacy skills, and encourage changes in learning patterns from passive to active. In addition, the findings also show that the learning process in Islamic boarding schools takes place comprehensively by integrating cognitive, affective, and spiritual aspects that are in accordance with the character of Generation Z. The collaborative and value-based environment of Islamic boarding schools also helps strengthen changes in student behavior. Overall, this study emphasizes that the integration of religious values ​​with an active learning approach can be an effective model in forming a generation that is adaptive, critical, and has noble character.